Lower East Side memories : a Jewish place in America - Diner, Hasia R (Princeton University Press, 2000)
"Manhattan's Lower East Side stands for Jewish experience in America. With the possible exception of African-Americans and Harlem, no ethnic group has been so thoroughly understood and imagined through a particular chunk of space. To learn when and why this dark warren of pushcartlined streets became an icon, Hasia Diner follows a wide trail of high and popular culture. She examines children's stories, novels, movies, museum exhibits, television shows, summer-camp reenactments, walking tours, consumer catalogues, and photos hung on deli walls far from Manhattan."--Jacket.